Spatial variability in the abundance and prey selection of the corallivorous snail Drupella spp. in the southeastern Hainan Island, China - Lei, Xinming; Liu, Chengyue; Zhang, Yuyang; Yu, Xiaolei; Yang, Jianhui; Luo, Yong; Zhou, Guowei; Huang, Hui (Frontiers in Marine Science, 2022)
Anthropogenic climate change has caused extensive loss of biodiversity and ecosystem function globally, particularly on coral reefs in shallow tropical waters. As the corallivorous snails represent considerable disturbances to coral reefs across Indo-Pacific region, it is becoming one of the threats to coral health and recovery in the Hainan Island, South China Sea, but current knowledge gap remains on the abundance distribution, prey preferences, and the influence factors related. Thus, we aimed to assess Drupella spp. distribution and abundance in relation to coral prey selectivity, abundance, availability and nutritional value. The snail density was heterogeneously distributed in the study area with an average of 0.72 ± 0.32 ind m-2 (varied from 0.09 ± 0.03 to 1.78 ± 0.39 ind m-2), and the snail density was found generally higher in locations with higher coral cover, while resulted in much lower density where their preferred corals became scarce. Despite the snails showed a positive preference to Acroporidae corals, they displayed dietary plasticity by changing with prey abundance and availability. Further, we found the electivity index of the coral prey related to the substrata condition, and the nutritional value of prey was an additional important determinant in the prey preference, suggesting that the specific reef habitat and environmental context may alter prey preference of Drupella spp. Combined, these results provide preliminary evidence that Drupella spp. is among the common corallivories in the reef regions of Hainan Island, and we recommend that large-scale monitoring programs assess the spatial-temporal trends to better understand the dynamics of predations linked to both the anthropogenic and natural impacts.